Joshua Davis: Author of Spare Parts - K-State First (Kansas State University, K-State First., 2016)
Flyer advertising Joshua Davis's author talk at Kansas State University.
Citation: K-State First (2016). Joshua Davis: Author of Spare Parts [Flier]. Manhattan, Kansas: K-State First.
Keywords: Spare Parts; Common reading program; Promotional materials; Joshua Davis; Promotional materials